Socioeconomic determinants that influence the agricultural practices of small farm families in northern Colombia (2021)
Access to agricultural services promotes agricultural production and livelihoods of smallholders in most developing countries. The purpose of this study was to analyze the socioeconomic determinants that influence the application of agricultural practices in peasant families in northern Colombia. Categorical and numerical variables of demographic information were evaluated at 200 Agricultural Production Units (APU) in the five prioritized municipalities. With the data obtained, multiple correspondence analysis (MCA) and principal component analysis (PCA) were performed. The results indicated heterogeneity in terms of farmer cooperative, socioeconomic factors and agricultural practices. The study found that education level, income from agriculture, farmer cooperative and credit were determinant factors for most of the agricultural practices that were considered. The results also indicate that non-agricultural income did not influence household well-being. It was found that extension services in the area of the study are insufficient and that farmers face difficulties in having access to credit and loans. Understanding of these factors is essential for the formulation and implementation of intervention strategies aimed at improving the quality of life of these communities, and to preserve and manage human, social, agricultural and financial capital.